Interferon Gamma Receptor: The Beginning of the Journey - Lamaze, Christophe; Blouin, Cédric M. (Frontiers in Immunology, 2013)
Our view of endocytosis and membrane trafficking of transmembrane receptors has dramatically changed over the last 20 years. Several new endocytic routes have been discovered and mechanistically characterized in mammalian cells. Long considered as a passive means to terminate signaling through down-regulation of the number of activated receptors at the plasma membrane, it is now established that receptor endocytosis and endosomal sorting can be directly linked to the regulation of intracellular signaling pathways. The functional links between membrane trafficking of interferon receptors and JAK/STAT signaling have recently begun to be unraveled. These studies raise the exciting possibility that a certain level of signal specificity can be achieved through endocytosis and selective localization of the activated complexes within cellular membranes. The ongoing development of high-resolution cell imaging techniques with better spatial and temporal resolution gives new means of deciphering the inherent complexity of membrane trafficking and signaling. This should help to better comprehend the molecular mechanisms by which endocytosis and endosomal sorting of interferon receptors can orchestrate signaling selectivity within the JAK/STAT pathway that can be activated by as many as 60 different cytokines, growth factors, and hormones.